Effect of low salicylate diet and blood salicylate level on the symptom control of chronic spontaneous urticaria - Guloglu, Sercan; Ozturk, Ayse Bilge; Incir, Said; Buyuktiryaki, Betul; Gelincik, Asli; Demir, Semra; Arik Yilmaz, Ebru; Uysal, Pinar; Arga, Mustafa; Cavkaytar, Ozlem; Gumusburun, Reyhan; Gokce, Tugba; et al. (Frontiers in Allergy, 2025)
BackgroundUp to 30% of chronic spontaneous urticaria (CSU) patients and 24% of children with CSU may have an NSAIDs-exacerbated cutaneous disease (NECD). Some vegetables and fruits are rich in salicylate. Salicylates in food can exacerbate symptoms in CSU patients.AimOur aim is to investigate the effect of a low salicylate diet on urticaria severity, quality of life, blood salicylate level and urine arachidonic acid pathway metabolites.MethodsPatients followed a fourweek low salicylate diet. Chronic urticaria quality of life questionnaire (CU-Q2oL) and 4 Days-Urticaria Activity Scores (UAS4) were recorded and blood and urine samples were collected at baseline and after the low salicylate diet. Urine Leukotriene-E4, Prostaglandin-E2, Prostaglandin-F2α, Thromboxane-A2, and creatinine levels were measured via ELISA. Blood salicylate level was determined by LC-MS/MS.ResultsA total of 36 CSU patients were included in the study. The CU-Q2oL scores significantly decreased from 33.7 to 20.7 (p < 0.001) and the UAS4 significantly decreased from 14 to 8 (p < 0.001) after low salicylate diet when compared to baseline (low scores mean less complaints). The blood salicylate level was significantly lower after the low salicylate diet compared to the baseline (p = 0.042). However, there was no significant effect of the diet on urinary LTE4, PGDE2, PGDF2α and TXA2 levels.ConclusionOur findings suggest that a low salicylate diet may help to reduce the severity of urticaria and improve quality of life by lowering blood salicylate levels. However, the diet had no impact on urinary LTE4, PGDE2, PGDF2α, and TXA2 levels.